Reclaimed asphalt pavement with waste frying oil and crumb rubber - Mohamed Bilema, Munder Abdullah (2021)
The application of Reclaimed Asphalt Pavement (RAP) has become a relatively standard material in the road industry in most countries. However, some of the problems associated with the addition of RAP to asphalt mixtures are the increase in moisture and cracking damage. The addition of rejuvenators into the recycled mixture containing RAP is also needed to enhance its performance although the rutting resistance remains a major issue. Therefore, there is a need to investigate the incorporation of other materials in the design of the asphalt mixture to achieve improved properties and better performance. This study was carried out to investigate the performance of the recycled asphalt mixture that consists of the conventional asphalt binder with 60/70 penetration grade, 25% and 40% RAP, and the incorporation of waste materials comprising 2.6% and 4.7% Waste Frying Oil (WFO) as the rejuvenator and 1.5% Crumb Rubber (CR) with sieve size of 0.15 mm as the modifier. The study was divided into three stages, namely evaluation of material properties, analysis of the asphalt binder properties, and determination and analysis of the asphalt mixture performance. Based on the results, the addition of 25% and 40% RAP in the asphalt mixture along with WFO and CR lowered the Indirect Tensile Strength (ITS) by 31.1% and 47.3%, respectively, which fulfilled the requirement of the ITS ratio test. The resilient modulus pattern for the recycled asphalt mixture containing WFO and CR was identical at 25 and 40 °C. When tested at 40 °C, the 25% and 40% RAP with incorporated WFO and CR generated a significant resilient modulus of 848 and 901 MPa, respectively. The recycled asphalt mixture with WFO and CR also exhibited a lower permanent strain than that of the virgin asphalt binder. The rutting values of all asphalt mixtures in the wheel tracking test demonstrated a similar pattern at 45 and 60 °C test temperatures. The rutting resistance of the recycled asphalt mixture with WFO and CR slightly improved compared to the virgin asphalt binder at 60 °C. Therefore, the incorporation of WFO and CR has a considerable influence on the RAP performance while preserving the environment and reducing pollution through the recycling of waste materials.